COVID-19, oxidative stress, and male reproductive dysfunctions: is vitamin C a potential remedy? - Sengupta, P; Dutta, S; Slama, P; Roychoudhury, S (Physiological research, 2022)
Few peculiarities have been observed in the etiology of coronavirus disease 2019 (COVID-19), one such being its greater prevalence in men than women partly due to the higher expressions of angiotensin-converting enzyme-2 (ACE2) in the male reproductive tissues. Recent scientific reports are in line with some of the evidence-based hypotheses in the initial phase of the COVID-19 pandemic, regarding the involvement of oxidative stress (OS) and oxidant-sensitive pathways in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection-mediated male reproductive disruptions. The seminal dissemination of SARS-CoV-2 or its components, testicular disruptions due to viral infection and oxidative damage in the testis have all been evidenced recently. High-dose of antioxidants, such as vitamin C, have been shown to be a useful treatment for COVID-19 patients, to alleviate systemic inflammation and OS. In addition, vitamin C is a major testicular antioxidant that neutralizes excess reactive oxygen species (ROS), prevents sperm agglutination, prevents lipid peroxidation, recycles vitamin E, and protects against DNA damage. Thus, the present review aims to discuss the mechanism of COVID-19-mediated male reproductive dysfunctions, based on the evidence available so far, and explore the possibility of using vitamin C in alleviating testicular OS and associated damage caused by COVID-19.
Keywords: Ascorbic Acid; farmakoterapie COVID-19; Oxidative Stress; pandemie; Female; kyselina askorbová; Pandemics; oxidační stres; Humans; ženské pohlaví; mužské pohlaví; SARS-CoV-2; lidé; Male; COVID-19 Drug Treatment